The study of waste composition in Joe Slovo Township, Nelson Mandela Bay Municipality, South Africa - Adeleye Ayoade Adeniran; Sibongangani Khonelihle Mngomezulu; Sijekula Mbanga; Winston Shakantu (Diponegoro University, 2023)
Household waste (HW) forms a vital part of municipal solid waste (MSW), and the inadequate management of HW poses a serious challenge in many developing cities. A study of the composition of HW is therefore vital in designing an effective solid waste management plan for cities and towns. A waste composition study is also important as estimating waste types produced and treatments applied can be an important tool for discerning what technology can be utilised for waste management trends. The study evaluated the composition of household solid waste generation in Joe Slovo township (JST) using a mixed-method research design to identify waste characteristics. The study's methodology included evaluating literature and administering structured questionnaires. The data were analysed using SPSS and presented in simple tables and charts. The waste typology produced by the residents are metals, papers, bottles, plastic materials, and food remains, among others. In addition, most waste typology produced by JST is recyclable. The results revealed that JST has no significant difference in the type of waste produced when comparing male and female respondents. The study recommends that the waste typology generated by JST can be utilised as a resource to develop economic income through recycling.